Anatomy of the smooth muscle structure in the female anorectal anterior wall: convergence and anterior extension of the internal anal sphincter and longitudinal muscle. (24th January 2019) - Muro, S.; Tsukada, Y.; Harada, M.; Ito, M.; Akita, K.
Abstract: Aim: The anatomy of the region between the vagina and anal canal plays an essential role when performing a proctectomy for low‐lying tumours. However, the anatomical characteristics of this area remain unclear. The purpose of the present study was to clarify the configuration, and both lateral and inferior extensions, of the muscle bundles in the anorectal anterior wall in females. Methods: Using cadaveric specimens, macroscopic anatomical and histological evaluations were conducted at the anatomy department of our institute. Macroscopic anatomical specimens were obtained from six female cadavers. Histological specimens were obtained from eight female cadavers. Results: The smooth muscle fibres of the internal anal sphincter and longitudinal muscle extended anteriorly in the anorectal anterior wall of females and the muscle bundles showed a convergent structure. The anterior extending smooth muscle fibres merged into the vaginal smooth muscle layer, distributed subcutaneously in the vaginal vestibule and perineum and spread to cover the anterior surface of the external anal sphincter and the levator ani muscle. Relatively sparse space was observed in the region anterolateral to the rectum on histological analysis. Conclusion: Smooth muscle fibres of the rectum and vagina are intermingled in the median plane, and there is relatively sparse space in the region anterolateral to the rectum. Therefore, when detaching the anorectal canal from the vagina during proctectomy, an approach from both the lateral sides should be used.